1996
DOI: 10.1002/(sici)1099-1026(199609)11:5<295::aid-ffj585>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Sulphur Compounds and some Uncommon Esters in Durian (Durio zibethinus Murr.)

Abstract: Forty-three sulphurcontaining constituents were found in a pentane extract of the durian fruit (Durio zibethinus Murr., Bombacaceae). Amongst them, 22 are new compounds. They belong to dialkyl di-and trisulphides, 3-(alkylthi0)-and 3-(alkyldithio)-butan-l-ols, 1,l-bis(a1kylthio)alkanes and 1-(alkylthi0)-1-(alkyldithio)alkanes, trithiolanes, tetrathiolanes and S-alkyl thioesters. In addition, the ethyl (Z,Z)-, (E,Z)and (E,E)-deca-2,4dienoates, ethyl (3Z,6Z)-decadienoate and the ethyl (E,Z,Z)and (E,E,Z)-decatrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Of the 108 volatiles compounds determined in durian, 18 organosulfides were identified, making sulfurous compounds the second major volatile constituents, after ester group ( 56 ). Durian from Indonesia was reported to contain 17 ( 55 ) and 43 ( 72 ) organosulfides in two individual studies, with some common organosulfides detected such as S -ethyl thioacetate, diethyl disulfide, and 3,5-dimethyl-1,2,4-trithiolane. The volatile constituents of three different durian varieties D15, D28, and D74 were compared and it was found that D28 has the highest organosulfides content ( 54 ).…”
Section: Brief Survey Of Organosulfides Rich Foodsmentioning
confidence: 99%
“…Of the 108 volatiles compounds determined in durian, 18 organosulfides were identified, making sulfurous compounds the second major volatile constituents, after ester group ( 56 ). Durian from Indonesia was reported to contain 17 ( 55 ) and 43 ( 72 ) organosulfides in two individual studies, with some common organosulfides detected such as S -ethyl thioacetate, diethyl disulfide, and 3,5-dimethyl-1,2,4-trithiolane. The volatile constituents of three different durian varieties D15, D28, and D74 were compared and it was found that D28 has the highest organosulfides content ( 54 ).…”
Section: Brief Survey Of Organosulfides Rich Foodsmentioning
confidence: 99%
“…[1][2][3][4] Indeed, the smell of durian fruit is considered to be so foul that it is refused to be transported on the Singapore subway system and by many airlines. 5 Packaging and storage of odorant food products is challenging and the concentration of odors may reach unbearable levels for the human olfactory system. Urbanisation and growing global transport of food products increase the demand for efficient odor eliminating strategies.…”
Section: Table Of Content: Introductionmentioning
confidence: 99%
“…In the durian in which the sulfur-containing volatiles predominated, diethyl disulfide, diethyl trisulfide, and 3,5-dimethyl-1,2,4-trithiolane were the major compounds with a relative composition of 28% to 88%, 8% to 24%, and 10% to 22%, respectively, similar to previous reports. 4,22 Diethyl disulfide has a sulfury, roast, and cabbage-like odor, while diethyl trisulfide has a sweet and alliaceous odor. Meanwhile, 3,5-dimethyl-1,2,4-trithiolane has a sulfury and onion-like odor.…”
Section: Resultsmentioning
confidence: 99%